Cognitive-behavioral, behavioral, and mindfulness-based therapies for menopausal depression: A review. Issue 1 (January 2015) - Green, Sheryl M.; Key, Brenda L.; McCabe, Randi E.
Abstract Menopause is a natural transition that all women go through in their lives that is often accompanied by a number of physical and emotional symptoms. Upwards of 40% of women report depression symptoms associated with menopause (Timur & Sahin, 2010) [1]. Treatments for menopausal depression include pharmacological agents such as antidepressants and hormone therapy (HT) as well as psychological approaches. This paper provides a review of cognitive-behavioral, behavioral, and mindfulness based (CBBMB) therapies in treating depression during the menopausal transition. After conducting an electronic database search, only two studies specifically using CBBMB methods were found, both had positive results. Since so few studies existed that specifically evaluated CBBMB treatments for menopausal depression (n = 2), a larger net was cast. Studies that assessed depression symptoms as an outcome measure in an evaluation of CBBMB treatments for hot flashes or menopausal symptoms more broadly, were included. The review revealed that interventions targeting hot flashes or menopausal symptoms using CBBMB methods mostly proved to have had a positive impact on depression symptoms in the mild range of severity. Directions for future research are discussed including the need for more CBBMB interventions targeting depression during the menopausal transition to establish their efficacy.